2004
DOI: 10.1111/j.0009-9163.2004.00223.x
|View full text |Cite
|
Sign up to set email alerts
|

The Δ>15 Kb deletion French Canadian founder mutation in familial hypercholesterolemia: rapid polymerase chain reaction‐based diagnostic assay and prevalence in Quebec

Abstract: Approximately one in 500 individuals in Western population has autosomal dominant familial hypercholesterolemia due to mutations in the low-density lipoprotein receptor (LDLR) gene. Screening for these mutations is hampered by their large number, except in founder populations. We identified the breakpoint of the >15 kb deletion involving the LDLR gene promoter and exon 1, responsible for more than 60% of French Canadian hypercholesterolemia cases, as well as the breakpoint of the 5 kb deletion of exons 2 and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…We used the reported method to detect ⌬Ͼ 15 kb in these five patients (13). We first found that each had the diagnostic 435 bp band that could only be amplified if the deletion was present (13), that each was heterozygous for this mutant fragment, and that the sequence of this fragment corresponded to ⌬Ͼ 15 kb (13) in all five subjects ( Fig. 3 ).…”
Section: Dna Sequence Break Point Confirmation In Fh Patients With Abmentioning
confidence: 99%
See 4 more Smart Citations
“…We used the reported method to detect ⌬Ͼ 15 kb in these five patients (13). We first found that each had the diagnostic 435 bp band that could only be amplified if the deletion was present (13), that each was heterozygous for this mutant fragment, and that the sequence of this fragment corresponded to ⌬Ͼ 15 kb (13) in all five subjects ( Fig. 3 ).…”
Section: Dna Sequence Break Point Confirmation In Fh Patients With Abmentioning
confidence: 99%
“…All of these patients had French surnames, leading us to consider that this particular MLPA pattern might have resulted from the Ͼ 15 kb deletion ( ⌬Ͼ 15 kb) at the 5 Ј end of the LDLR . This deletion is the most common cause of FH in French Canadians (1,13). We used the reported method (13) to sequence the deletion break points in these five patients.…”
Section: Dna Sequence Confirmation Of Deletion Break Pointmentioning
confidence: 99%
See 3 more Smart Citations